Percutaneous Nephrostomy for Treatment of Posttransplant Ureteral Obstructions - Mostafa, Seyed Abulghasem; Abbaszadeh, Shahin; Taheri, Saeed; Nourbala, Mohammad Hossein (Urology Journal, 2008)
Introduction: We report our experience with percutaneous management of urologic complications following kidney transplantation. Materials and Methods: Of 1402 consecutive kidney transplant recipients from living donors at our hospital, 21 required percutaneous nephrostomy (PCN) for the treatment of obstructive lymphocele (n = 11), urinary calculus (n = 8), and stricture of the ureterovesical junction anastomosis (n = 2). We had also 11 kidney recipients with urine leakage from the ureter who were treated only by indwelling ureteral catheter. Urinary complications were diagnosed based on the clinical symptoms, elevated serum creatinine levels, ultrasonography and renal scintigraphy. Patients with ureteral obstruction or urine leakage were compared with kidney recipients without urologic complications. Results: A mean decline of 3.1 Â± 3.0 mg/dL (range, 0.1 to 10.7 mg/dL) in serum creatinine level was detected (P < .001) after PCN. All of the patients remained symptom free for a mean follow-up period of 34.2 Â± 20.1 months (range, 3 to 81 months). Patient and graft survival rates were not different between the patients undergoing PCN and other kidney recipients. The only difference was the history of using antilymphocyte globulin which was significantly more frequent in the patients of the PCN group (P = .01). Conclusion: In our experience, PCN is a safe and effective method for the treatment of ureteral obstructions in kidney allograft recipients. This method provided long-term success with few recurrences and low morbidity and mortality rates.